Power Injection Method-based evaluation of the effect of binding technique on the Coupling Loss Factors and Damping Loss Factors in Statistical Energy Anal-ysis simulations - Treszkai, Marcell Ferenc; Peiffer, Alexander; Feszty, Daniel (Manufacturing Technology Journal, 2021)
Measurement results on the Damping Loss Factor (DLF) and Coupling Loss Factor (CLF) between two steel plates is presented for 19 different junction types. The junctions involve joining technologies as line welding, point welding, bolting, riveting, gluing or their combinations, with parameters, such as spac-ing between the junction points or the angle between the plates varying. From the measurement results the DLF and CLF values were calculated by the Power Injection Method for the purposes of being ap-plied in Statistical Energy Analysis simulations. Four excitations were applied at each subsystem by impact hammer, while the response was recorded at sixteen response points at each subsystem. The measured CLF values were compared to each other from various aspects. Data were compared to the results obtained from SEA simulations by using the built-in analytical formulas. In general, good com-parison was observed, although the results appeared to be somewhat dependent on the frequency band. Finally, it was examined whether replacing the DLF values with data obtained for an uncoupled flat plate as well the CLF values with data from analytical formulas leads to acceptable accuracy of the re-sults.
Keywords: Statistical Energy Analysis; Damping Loss Factor; Coupling Loss Factor; Junction types; Vibration